Pengaruh keterlibatan ayah dalam pengasuhan (father involvement) terhadap konsep diri remaja - Ayu Isnaini; Nawang Warsi Wulandari; Deasy Christia Sera (University of Merdeka Malang, 2021)
Teenagers are individuals aged 13 to 22 years. One that becomes important in the development of adolescents is self-concept. Negative self-concept is possible to make teenagers experience despair, anxiety, to depression. The concept of self is formed from individuals as children, therefore parents become the first place in the formation of self-concept. Not only the mother, but the involvement of fathers in parenting also has a considerable influence on the development of children. This quantitative research was conducted to determine the effect of the involvement of fathers in parenting on adolescent self-concept. The research measuring instrument uses a Likert scale concerning aspects of father involvement in parenting and self-concept of adolescents. The results of the study of 115 subjects showed a significance of 0.00 0.05 meaning that there was an influence of the father's involvement variable in parenting to the self-concept variable. The value of R square shows 0.487 or 48.7% including the quite significant category.